(a+b+c) ^3, find with proof
Answers
Answered by
1
Algebra,
We have,
(a+b+c)³
Have to proof,
a³+ b³+ c³+ 3(a+b)(b+c)(c+a)
Now,
(a+b+c)³
= {a+(b+c)}³
= a³+(b+c)³+3a(b+c){a+(b+c)}
= a³+b³+c³+3bc(b+c)+3ab{a(b+c)}+3ac{a(b+c)}
= a³+b³+c³+3bc(b+c)+3a²b+3ab(b+c)+3a²c+3ac(b+c)
= a³+b³+c³+3bc(b+c)+3ab(b+c)+3ac(b+c)+3a²b+3a²c
= a³+b³+c³+3bc(b+c)+3ab(b+c)+3ac(b+c)+3a²(b+c)
= a³+b³+c³+3(b+c)(bc+ab+ac+a²)
= a³+b³+c³+3(b+c){b(a+c)+a(a+c)}
= a³+b³+c³+3(b+c)(a+c)(b+a)
= a³+b³+c³+3(a+b)(b+c)(c+a) [proved]
That's it
Hope it helped (≧▽≦)
We have,
(a+b+c)³
Have to proof,
a³+ b³+ c³+ 3(a+b)(b+c)(c+a)
Now,
(a+b+c)³
= {a+(b+c)}³
= a³+(b+c)³+3a(b+c){a+(b+c)}
= a³+b³+c³+3bc(b+c)+3ab{a(b+c)}+3ac{a(b+c)}
= a³+b³+c³+3bc(b+c)+3a²b+3ab(b+c)+3a²c+3ac(b+c)
= a³+b³+c³+3bc(b+c)+3ab(b+c)+3ac(b+c)+3a²b+3a²c
= a³+b³+c³+3bc(b+c)+3ab(b+c)+3ac(b+c)+3a²(b+c)
= a³+b³+c³+3(b+c)(bc+ab+ac+a²)
= a³+b³+c³+3(b+c){b(a+c)+a(a+c)}
= a³+b³+c³+3(b+c)(a+c)(b+a)
= a³+b³+c³+3(a+b)(b+c)(c+a) [proved]
That's it
Hope it helped (≧▽≦)
Attachments:
![](https://hi-static.z-dn.net/files/d69/9e26848a9d1669c49cf586dee1e6f702.jpg)
Similar questions